Sociabilités populaires et relations électives - Béatrice Laville (Flaubert: Revue Critique et Génétique, 2021)
This article proposes to analyse the question of popular sociability in Zolian fiction. In addition to the question of the spaces where the dramatisation of social relations is played out with its codes and rites and the processes of domination inherent in the life of the groups, the question of money and with it, gain, debt and expenditure, imposes itself as a regulation of the modes of relation. A motor for altering sociability and a powerful agent of dramatisation, the representation of money expresses the economic violence of a system that feeds on the alienation of individuals.